Literature Review: The Relationship between Eating Habits and Dyspepsia in Adolescents - Rahmat Hidayat; Agung Susanto; Anik Lestari (Amerta Nutrition, 2023)
Background: All over the world the prevalence of dyspepsia is quite high. Various literature sources in western countries show that the prevalence of dyspepsia Various literature sources in western countries show that the prevalence of dyspepsia is in the range of 7-41% in 2009, but unfortunately only about 10-20% of patients seek treatment or medical help. The increasing condition of dyspepsia can cause various health problems such as decreasing quality of life and functional activity. Dyspepsia usually affects those of productive age.